Edukasi Pemasaran Online Bagi Pelaku Bisnis UMKM - Vina Lili Handayani; Muhammad Syarofi (BAHRI: Jurnal Pengabdian Kepada Masyarakat, 2024)
The presence of the ASEAN Economic Community and the Industrial Revolution 4.0 has changed the dynamics of business and marketing, so that strategic steps are needed to help MSMEs, especially in Sidomulyo Village, to remain competitive in the digital era, and be able to compete competitively in the digital era. This Community Service Program aims to help MSME actors improve their personal skills and business capacity. One of the MSMEs that consistently maintains and develops local potential-based businesses is community-based entrepreneurial businesses that produce products and services. The service process begins with collecting initial data through interviews and observations to find out more about business conditions, then continues with conducting this research through the ECA-EVARED technique (Exploration, Creat and Action, Evaluation, and Report and Dissemination) and business assistance in order to improve the ability of business actors to market online. The results of the community service program for MSME actors in Sidomulyo are that marketing is getting wider, helping the economy of small traders, they can already market through digital marketplaces, income is increasing and MSME actors are more creative in marketing their products.